Life expectancy in children with cerebral palsy. - Hutton, J. L. (BMJ Group, 1994)
OBJECTIVE--To determine life expectancy of children with cerebral palsy. DESIGN--Cohort analysis, by means of register compiled from multiple sources of ascertainment, of all children with cerebral palsy born during 1966-84 to mothers resident in Mersey region. Status of children was determined by flagging through NHS central register. SUBJECTS--1258 subjects with idiopathic cerebral palsy, of whom 1251 were traced and included in analysis. MAIN OUTCOME MEASURES--Effect of functional ability (ambulation, manual dexterity, and mental ability), sex, birth weight, and gestational age on survival. RESULTS--20 year survival for whole cohort was 89.3% for females and 86.9% for males. For subjects with no severe functional disabilities 20 year survival was 99% (95% confidence interval 98% to 100%), while subjects severely disabled in all three functional groups had 20 year survival of 50% (42% to 58%). Subjects with birth weight < or = 2500 g had 20 year survival of 92% (89% to 95%), while those with birth weight > 2500 g had survival of 87% (84% to 89%). Subjects with gestational age of > 37 weeks had 20 year survival of 93% (91% to 96%), while those with gestational age > or = 37 weeks had survival of 85% (83% to 88%). Birth weight and gestational age were less predictive of survival than functional disability. Best statistical model used gestational age and number of severe functional disabilities as predictors. CONCLUSIONS--Life expectancy of this cohort of children with cerebral palsy was greater than has been suggested in some previous studies. This has important implications for social, educational, and health services.